Kemampuan Berpikir Kritis dalam Pembelajaran Matematika melalui Pendekatan Contextual Teaching and Learning - Annisah Dian Oktaviani; Shoffan Shoffa; Febriana Kristanti (Journal of Education and Teaching (JET), 2023)
This study explains how to improve critical thinking skills in junior high and high school students. The purpose of this study was to determine students' critical thinking skills in learning mathematics, especially at the junior and senior high school levels. The method used in this research is a literature study. The researcher concluded that the ability to think critically in learning mathematics can make students more active in learning. The critical thinking stage in learning mathematics goes through four stages, namely giving questions, dividing groups, thinking together, and giving answers. The conclusion of this research is evident from the results of another research that has been done before.